Depreciation of Non-Current Assets: Harmonization of International Practices and Regulatory in Ukraine - ZADOROZHNII, Zenoviy Mikhailo; KAFKA, Sofiia (Journal of Advanced Research in Management; Vol 7 No 1 (2016): JARM Volume VII Issue 1(13) Summer 2016, 2017)
In the conditions of globalization, the application of international accounting standards and reporting on the enterprises business activity is becoming topical in order to take into account the different users’ needs in information for administrative decision-making. The conceptual framework of financial statements of different enterprises have to be comparable, otherwise the information is not relevant for management demands. The application of International Standards of Accounting and Reporting allows understanding the statements of different companies; compare them, to make management decisions. However, in Ukraine and several other countries the national accounting standards, regulatory acts are being operated containing different provisions for regulation of accounting objects. So, the organizational and methodological principles of accrual and accounting of intangible assets amortization require to be investigated because it is an important factor affecting the results of financial and economic activity of the companies. The main purpose of the study is to systematize the international and national practice of charging and accounting depreciation of fixed assets of enterprises, singling out the differences between them, comparing depreciation methods considering their strengths and weaknesses, identification of improvement trends in accounting depreciation of enterprise fixed assets. The general scientific and special methods of analysis have become the methods of study. The methodological basis of investigation is the scientific treatments of researchers in economics, international, legal and regulatory acts of Ukraine. The concrete proposals for improvement of legal and regulatory acts of Ukraine on accounting and depreciation of fixed assets for the unification of international and national requirements have become the results of the investigation. The authors have come to the conclusion of the necessity of creating a depreciation fund with real financial support for carrying out the effective depreciation policy at the enterprise. The mechanism of calculating the average depreciation ratio has been determined by multiplying it and the cost of the sold production to fix the amount of depreciation that can be used to update the fixed assets and etc. It has been proposed to adapt the legislative regulation of accounting depreciation to the international practice to avoid ambiguity.